PELAKSANAAN ITSBAT NIKAH DI PENGADILAN AGAMA RENGAT KABUPATEN INDRAGIRI HULU - Novrida Fauziyah Nasution; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Marriage according to the Marriage Act aims to establish a happy family and eternal divinity by the Almighty. Marriage Law Article 2 Clause 1 and 2 state that marriage valid if done according to the law of each religion and belief and every marriage is recorded in accordance with the laws and undangan.Itsbat Nikah stated explicitly in the Compilation of Islamic Law, published in Article 1 Section 2, which states that in the case of a marriage that can not be proved by a marriage certificate can be submitted Ithbat illegitimate Religious Courts.The purpose of this study to determine the Implementation Ithbat Marriage Religious Court Rengat Indragiri Hulu and to identify constraints in check Ithbat Marriage Religious Court Rengat Indragiri Hulu.This research method or empirical sociological research, legal research field that studies of legal identification. The research location in the Religious Court Rengat Indragiri Hulu because many Ithbat marriage petition is filed, investigated using population and sample.Results of research and discussion shows that the implementation of Marriage in the Religious Ithbat Rengat Indragiri Hulu has not run as it should be because in 2014 many application for approval of marriage for the sake of the maintenance of the child's birth certificate, the administration of the pilgrimage and therefore do not have a marriage certificate. But not all requests can be granted by a religious court, it is associated constraints experienced by the religious court in determining the legitimacy of a marriage, while these obstacles because the witness who had died, the husband and wife earlier would not be present at the hearing and the applicant Ithbat Marriage can not prove the legitimate guardians of religion Islam.Permohonan Ithbat marriage that can be submitted to the Court of religion is the existence of marriage in the context of a divorce settlement, the loss of a marriage certificate, any doubts about the legitimacy of one of the conditions of marriage, the marriage that occurred prior to the enactment of Law No. 1 In 1974, a marriage that is done by those who do not have a marriage impediment under the Act, the Marriage under dlakukan hands after the enactment of Law No. 1 of 1974 on Marriage.